The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.jnnfm.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and numerical investigation of the dynamics of microconfined droplets in systems with one viscoelastic phase

Abstract: a b s t r a c tThe dynamics of single droplets in a bounded shear flow is experimentally and numerically investigated for blends that contain one viscoelastic component. Results are presented for systems with a viscosity ratio of 1.5 and a Deborah number for the viscoelastic phase of 1. The numerical algorithm is a volumeof-fluid method for tracking the placement of the two liquids. First, we demonstrate the validation of the code with an existing boundary integral method and with experimental data for confine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 53 publications
(121 reference statements)
3
17
0
Order By: Relevance
“…As a consequence of the symmetry, the streamlines coming from the left and right show the same behavior. Similar large recirculation zones at the front and rear of a droplet were already reported from 3D numerical simulations of the flow field around a single highly confined droplet [46]. This large recirculation zone, present in confined conditions, causes the offset to decrease during approach of the droplets, as can be seen in Fig.…”
Section: δX/2r (-)supporting
confidence: 83%
“…As a consequence of the symmetry, the streamlines coming from the left and right show the same behavior. Similar large recirculation zones at the front and rear of a droplet were already reported from 3D numerical simulations of the flow field around a single highly confined droplet [46]. This large recirculation zone, present in confined conditions, causes the offset to decrease during approach of the droplets, as can be seen in Fig.…”
Section: δX/2r (-)supporting
confidence: 83%
“…From numerical simulations for droplets that have attained a steady state shape in a subcritical shear flow, it is known that the viscoelastic stresses in and around the droplet increase with confinement whereas their location remains approximately the same. [33] For an unbounded viscoelastic droplet close to breakup, Verhulst et al [38] have shown that during elongation of the droplet, the viscoelastic stresses in the droplet shift from the droplet tips toward the thinning center of the droplet, thereby stabilizing it against necking. This is schematically depicted in Figure 6a.…”
Section: Comparison Of the Effects Of Component And Interfacial Rheologymentioning
confidence: 99%
“…Although theoretical and numerical studies of droplet dynamics that take into account one of the aforementioned complexities are readily available (see for instance [20,[28][29][30][31][32] and references therein), a limited amount of numerical studies consider their combined effects. [25,26,33,34] Concerning droplet breakup, no results are available in this respect, neither from experimental nor from numerical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Verhulst et al and Cardinaels et al considered fully three‐dimensional shear‐driven droplets in which either the droplet or the surrounding fluid is viscoelastic. The Oldroyd‐B model is employed in the present study to facilitate a direct comparison with the results of the work of Verhulst et al and Cardinaels et al The spherical droplet of radius R is at the center of the computational domain. Opposite velocities, ie, V and − V , are enforced on the two walls located at z = 0 and z = H to obtain the shear rate trueγ˙=2Vfalse/H.…”
Section: Validationmentioning
confidence: 99%
“…Periodic boundary conditions are imposed in the x (spanwise) and y (streamwise) directions and no‐slip conditions at the two walls. Following the works of Verhulst et al and Cardinaels et al, the nondimensional parameters are defined as follows. The Reynolds number Re=ρ1trueγ˙R2false/μ1, the capillary number Ca=Rtrueγ˙μ1false/σ, the Weissenberg number Wi=λtrueγ˙, the viscosity ratio k μ = μ 2 / μ 1 , the density ratio k ρ = ρ 2 / ρ 1 , and the confinement ratio χ = 2 R / H .…”
Section: Validationmentioning
confidence: 99%